HUBUNGAN OBESITAS DAN UMUR DENGAN KEJADIAN DIABETES MELLITUS TIPE II - Putri Dafriani (Jurnal Kesehatan Medika Saintika, 2017)
ABSTRACT Nowaday, every year the rate of DM (Diabetes Mellitus) always rise. DM is one of the fourth biggest caused of human died. There are some factors which are caused it. Some of them are obesity and age. obesity  is able to be identified by measuring BMI. For DM type II risky catogorize if BMI> 25 kg/m2. The risky age factor appears to the patients in the age up to 40 years old. The aim of this research is to know the correlation between obecity and age with the DM incident rate in 2017.The method of this research is analitical method by using cross sectional study which will be applied in Health Center of Gambok of Sijunjung regency on February 2017.The sampling which will be done is accidental sampling and have 90 sampple. The process implied are editing, coding, entry, cleaning, and analysis of univarat and bivarat which is done by calculating statitics with chi-square(X²) and P<0,005.The result of the research is found that 10% of respondents have DM, 90% of respondent not DM and 38,9% of respondents have obecity, 61,1% of respondents have not obecity, 50% of respondents included into the risky age, and 50% of respondents included into the non risky age. In the Bivariat analysis, it is found that there is a significant correlation between obecity and the DM type II incident rate with P= 0,025 and there is a signifant correlation with DM type II incident rate with P=0,031.Through this study, the author concluded that there is a significant correlation between obesity and age with DM type II.  The Health  Center of Gambok should give illumination which emphasizes on how to keep the healthy life, either  includes physical activity or healthy diet so that the rate of obesity will be decreased and and examination of sugar level periodically for the patients of DM tipe II classified. Keyword          : Obesity, Age,  Diabetes Mellitus ABSTRAK Kejadian diabetes mellitus (DM)  mengalami peningkatan dari hari ke hari. DM termasuk empat besar penyebab kematian. Ada beberapa faktor penyebab terjadinya DM diantaranya adalah faktor usia dan obesitas. Penelitian ini bertujuan untuk mengetahui hubungan antara faktor usia dan obesitas dengan kejadian DM pada pasien DM di Puskesmas    Gombok  Kabupaten Sijunjung tahun 2017.Metode penelitian ini adalah observasi dengan pendekatan cross secsional. Sampelnya berjumlah 90 orang yang diambil dengan teknik accidental sampling. Uji chi- square digunakan untuk melihat hubungan antara variabel independen dengan dependen.Hasil penelitian didapatkan 10% sampel menderita DM, 38,9% obesitas dan 50% memiliki usia yang beresiko. Analisis statistik didapatkan nilai p= 0,025 untuk hubungan obesitas dengan kejadian DM dan p=0,031 untuk hubungan usia dengan kejadian DM.Dari penelitian ini dapat disimpulkan ada hubungan antara faktor usia dan obesitas dengan kejadian DM. Diharapkan kepada petugas kesehatan dapat memberikan penyuluhan kepada masyarakat terutama dengan kelompok usia yang beresiko agar dapat menjaga pola hidupnya terutama mencegah terjadinya obesitas.